35th AIAA Applied Aerodynamics Conference 2017
DOI: 10.2514/6.2017-3258
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic Shape Optimization of a Box-Wing Regional Aircraft Based on the Reynolds-Averaged Navier-Stokes Equations

Abstract: The box wing is an unconventional aircraft configuration that has the potential to provide major savings in fuel consumption relative to the conventional cantilever wing. In order to further develop and evaluate this potential, high-fidelity aerodynamic shape optimization is applied to the aerodynamic design of a box wing and a cantilever wing, based on the Embraer E190 regional jet, with the latter serving as a performance baseline. The optimization framework consists of B-spline parameterization, free-form a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Due to the fluid nature of the initial design process, it is not recommended to use high fidelity analysis design tools, such as Computational Fluid Dynamics (CFD), at this stage as they can be unnecessarily costly [4,54]. What is required is a tool that strikes a balance between sufficient accuracy and computational cost [55][56][57][58]. Piperni et al [59] and Zhang et al [60] have argued that the level of fidelity that should be delivered by the models is mostly determined at the development stage, which the design process aims to enhance.…”
Section: Particles Selection Schema On I-mopso Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the fluid nature of the initial design process, it is not recommended to use high fidelity analysis design tools, such as Computational Fluid Dynamics (CFD), at this stage as they can be unnecessarily costly [4,54]. What is required is a tool that strikes a balance between sufficient accuracy and computational cost [55][56][57][58]. Piperni et al [59] and Zhang et al [60] have argued that the level of fidelity that should be delivered by the models is mostly determined at the development stage, which the design process aims to enhance.…”
Section: Particles Selection Schema On I-mopso Interfacementioning
confidence: 99%
“…Due to the fluid nature of the initial design process, it is not recommended to use high fidelity analysis design tools, such as Computational Fluid Dynamics (CFD), at this stage as they can be unnecessarily costly [4,54]. What is required is a tool that strikes a balance between sufficient accuracy and computational cost [55][56][57][58].…”
Section: Automated Optimisation Framework (Non-interactive)mentioning
confidence: 99%
“…In particular, the recent EU project PARSIFAL explored rather extensively the so-called Prandtl Plane concept, which was investigated from various angles, including market perspectives [9], conceptual design viewpoints [10][11][12], and more technical aspects (e.g., performance [13], stability [14], aerodynamics [15,16], structures [17]). Additionally, more specific studies were conducted by several universities, worldwide; several works investigated the BWA concept from design perspectives [20][21][22][23][24][25][26][27] whereas others focused on more specific things such as the aerodynamic efficiency of the box-wing itself [28][29][30][31][32][33][34], as well as structural [35,36] and stability [37][38][39][40] aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In [43,44], the authors reported developing a strategy that used non-interactive and interactive techniques, respectively, to formulate the design problem and improve the optimisation speed. To deliver a sufficient level of fidelity to the DM at very fast computational times, the low fidelity flow solver Athena Vortex Lattice (AVL) was used to capture the physics of the problem [45][46][47][48]. Improving the ability of the developed method to accelerate the search while retaining all the useful information in the design space was the main area of work.…”
Section: Introductionmentioning
confidence: 99%
“…The flow solver used to evaluate worthwhile solutions is the Athena Vortex Lattice (AVL) [51,52]. Many codes utilize Vortex Lattice Method (VLM) for aerodynamic characteristics calculations, but AVL is the most well-known and provides the most accurate and efficient results when compared with other aerodynamic analysis software employing the same method [45][46][47][48]52]. In addition, AVL code is easy to use and capable of manipulating a large number of design parameters within a short computational time and limited cost.…”
Section: Introductionmentioning
confidence: 99%